City Developments Limited: A journey in sustainable business development - HWANG, Soo Chiat (Institutional Knowledge at Singapore Management University, 2013)
City Developments Limited (CDL), one of Singapore’s leading international property and hotel conglomerates involved in real estate development and investment, hotel ownership and management, facilities management and the provision of hospitality solutions, has developed over 22,000 luxurious and quality homes in Singapore, catering to a wide range of market segments. CDL is widely recognised as a champion of sustainable practices in Singapore. It was the first company honoured with the President’s Social Service Award and President’s Award for the Environment in 2007. It was also the only developer to be accorded the Built Environment Leadership Platinum Award in 2009 and Green Mark Platinum Champion Award in 2011 by the Building and Construction Authority, the governing authority for Singapore’s built environment. CDL was the first Singaporean company to be listed on all three of the world’s top sustainability benchmarks - FTSE4Good Index Series since 2002, Global 100 Most Sustainable Corporations in the World since 2010 and the Dow Jones Sustainability Indexes since 2011. What are the key factors that have enabled CDL to successfully manage its journey in sustainable business development? How can the company continue to reinforce the culture of sustainability that it prided itself on? What could it do to increase awareness of their sustainability vision in the stakeholders?